The Role of Pomegranate Fruit in Human Health - Marufjanov Abdurakhman Mosinjon ugli (Web of Journals Publishing, 2023)
For pomegranate seedlings, cuttings are selected from fruitful, healthy bushes selected in advance from the pomegranate orchard. Among fruits, pomegranate is a subtropical crop. Pomegranate juice restores appetite, lowers body temperature and blood pressure, reduces the damage caused by viruses and microbes in the stomach. In the world of medicine, the juice of the sweet pomegranate fruit removes existing stones from the kidney, urinary tract, and gallbladder.